Analysis of influence of subway station deep foundation pit excavation on adjacent bridge piles. Issue 1 (March 2020) - Li, B; Sun, W; Li, G K
Abstract: Based on the engineering background of the deep foundation pit construction of Shenyang metro Line 10, the numerical simulation software Midas the GTS NX, and the three-dimensional integral calculation model considering the interaction of foundation pit supporting structure, surrounding soil and viaduct is established, and the numerical simulation value and the measured data are compared and analyzed, the applicability of the model is verified, the influence of foundation pit excavation on the deformation of pile foundation is studied, and the optimization scheme is given. The construction plan of Simulation + forecast is established to guide the practical construction of the project. The results show that when the depth of the pile foundation is 1.5 times the depth of the foundation pit, and the horizontal displacement of the pile foundation is within 1/2 of the control value, this is the optimal depth of the pile foundation. This is the minimum standard safe distance when the pier is 1/2 from the depth of the foundation pit.